2018
DOI: 10.1038/s41433-018-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

‘Statins in retinal disease’

Abstract: Statins are known for their blood cholesterol-lowering effect and are widely used in patients with cardiovascular and metabolic diseases. Research over the past three decades shows that statins have diverse effects on different pathophysiological pathways involved in angiogenesis, inflammation, apoptosis, and anti-oxidation, leading to new therapeutic options. Recently, statins have attracted considerable attention for their immunomodulatory effect. Since immune reactivity has been implicated in a number of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…A recent systematic review and meta-analysis found no differences in triglycerides, serum total cholesterol, and high-density lipoprotein cholesterol among patients with or without DR [35]. However, many studies have shown how using lipid-lowering medication, such as statins [171173] or fenofibrate [35, 173], reduce DR progression. Recently, a study used an animal model and described how fenofibrate inhibited the expression of NF- κ B and inflammatory chemokines, and also reduced oxidative damage in lipids, DNA, and proteins in diabetic retinas [174].…”
Section: Present and Future Therapeutic Targetsmentioning
confidence: 99%
“…A recent systematic review and meta-analysis found no differences in triglycerides, serum total cholesterol, and high-density lipoprotein cholesterol among patients with or without DR [35]. However, many studies have shown how using lipid-lowering medication, such as statins [171173] or fenofibrate [35, 173], reduce DR progression. Recently, a study used an animal model and described how fenofibrate inhibited the expression of NF- κ B and inflammatory chemokines, and also reduced oxidative damage in lipids, DNA, and proteins in diabetic retinas [174].…”
Section: Present and Future Therapeutic Targetsmentioning
confidence: 99%
“…The environmental/lifestyle factors described as capable of influencing the induction and/or progression of AMD include smoking, obesity, high fat, low antioxidant diet, and exposure to UV and blue light (reviewed in [13]). Some cardiovascular, immunological, and inflammatory biomarkers are reported to be linked to AMD [1416]. However, except for age, familial history, genetic predisposition, and smoking, other AMD risk factors are still controversial and require further study to confirm their involvement in AMD pathogenesis.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…In addition to their anti-inflammatory action, statins may have a protective effect on the microvascular endothelium in retinal ischemia models, thereby preventing pathological neovascularization [ 22 ]. Low doses of statins promoted vascular repair mechanisms by upregulating nitric oxide (NO) and vascular endothelial growth factor (VEGF) levels [ 23 ].…”
Section: Introductionmentioning
confidence: 99%